A comparison of animal personality and coping styles in the red junglefowl. (August 2017) - Zidar, Josefina; Balogh, Alexandra; Favati, Anna; Jensen, Per; Leimar, Olof; Løvlie, Hanne
Abstract : There is an increased focus in biology on consistent behavioural variation. Several terms are used to describe this variation, including animal personality and coping style. Both terms describe between-individual consistency in behavioural variation; however, they differ in the behavioural assays typically used, the expected distribution of response variables, and whether they incorporate variation in behavioural flexibility. Despite these differences, the terms are often used interchangeably. We conducted experiments using juvenile and adult red junglefowl, Gallus gallus, as subjects to explore the degree to which animal personality and coping styles overlap. We demonstrate that animal personality and coping styles can be described in this species, and that shyer individuals had more flexible responses, as expected for coping styles. Behavioural responses from both personality and coping style assays had continuous distributions, and were not clearly separated into two types. Behavioural traits were not correlated and, hence, there was no evidence of a behavioural syndrome. Further, behavioural responses obtained in personality assays did not correlate with those from coping style tests. Animal personality and coping styles are therefore not synonymous in the red junglefowl. We suggest that the terms animal personality and coping style are not equivalent and should not be used interchangeably. Highlights: Animal personality and coping style both describe consistency in behaviour. We assay behaviour of red junglefowl in personality and coping style tests. We observe both personality and coping styles in the red junglefowl. We show that personality and coping styles are not synonymous in the red junglefowl.